Restraining Police Use of Lethal Force and the Moral Problem of Militarization - Ford, Shannon (2022)
I defend the view that a significant ethical distinction can be made between justified killing in self-defense and police use of lethal force. I start by opposing the belief that police use of lethal force is morally justified on the basis of self-defense. Then I demonstrate that the state’s monopoly on the use of force within a given jurisdiction invests police officers with responsibilities that go beyond what morality requires of the average person. I argue that the police should primarily be concerned with preserving public safety. As a consequence, police have additional moral permissions to use lethal force. But this also means that the principle of restraint is inherent to the policing function and therefore police are obliged to go to greater lengths to avoid killing. I concede that the just use of police force can be made difficult in extreme situations such as a mass riot. In such cases, police should take proportionate actions necessary to protect the lives of inhabitants by restoring order, which might include calling on military support. I conclude with a cautionary note opposing militarization of the policing role.